2014
DOI: 10.1590/0074-0276130511
|View full text |Cite
|
Sign up to set email alerts
|

Sandflies (Diptera: Psychodidae) associated with opossum nests at urban sites in southeastern Brazil: a risk factor for urban and periurban zoonotic Leishmania transmission?

Abstract: Sandflies associated with opossum nests are reported for the first time in the yards of residences located in the urban area of the municipality of Monte Mor, situated in the metropolitan region of Campinas, state of São Paulo, Brazil. Eleven specimens of Evandromyia cortelezzii and one of Evandromyia lenti were captured in two Didelphis albiventris nests. Ev. cortelezzii is considered a secondary vector species for the transmission of Leishmania (Viannia) braziliensis and Leishmania (Leishmania) infantum in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…cortellezzii was identified in the kennels. Although only one specimen was found in association with the dogs, this phlebotomine species had previously been found in the urban area of Monte Mor, in opossum shelters located in the backyards of human houses (Cutolo et al, 2014). The association between Ev.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…cortellezzii was identified in the kennels. Although only one specimen was found in association with the dogs, this phlebotomine species had previously been found in the urban area of Monte Mor, in opossum shelters located in the backyards of human houses (Cutolo et al, 2014). The association between Ev.…”
Section: Discussionmentioning
confidence: 88%
“…Molecular methods have proven to be efficient for determining the presence, quantity and/or genotyping of Leishmania species that cause infections, since they are sensitive and specific (Gomes et al, 2007;Gomes et al, 2008;Cutolo et al, 2014). In this study, we reported identifying L. (V.) braziliensis in biopsied skin samples from dogs, from the border of active cutaneous lesions and from healing skin ulcers.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings agree with other studies that reported joint captures of phlebotominae and these mammal species, such as Ferreira et al (2015) who found infected small mammals (R. rattus, M. musculus, D. albiventris, and other species), and mentioned that in the same area and period, Ny. whitmani was the main phlebotominae species captured; and Cutolo et al (2014), who reported captures of phlebotominae of the genus Evandromyia associated with D. albiventris nests in an urban area of Brazil.…”
Section: Discussionmentioning
confidence: 99%